2021
DOI: 10.3390/molecules26103001
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect and Antioxidant Potency of Fermented Cultured Wild Ginseng Root Extracts of Panax ginseng C.A. Meyer in Mice

Abstract: Wild ginseng has better pharmacological effects than cultivated ginseng. However, its industrialization is limited by the inability to grow wild ginseng on a large scale. Herein, we demonstrate how to optimize ginseng production through cultivation, and how to enhance the concentrations of specific ginsenosides through fermentation. In the study, we also evaluated the ability of fermented cultured wild ginseng root extract (HLJG0701-β) to inhibit acetylcholinesterase (AChE), as well as its neuroprotective effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 98 publications
(111 reference statements)
0
13
0
Order By: Relevance
“…Notoginsenoside R1 increased choline acetyl transferase expression thereby increasing acetylcholine level, in an APP/PS1 double-transgenic mouse model of AD as compared to the vehicle-treated mice [ 121 ]. Polyacetylene compounds in hexane and methanol extracts of ginseng were reported to inhibit AChE [ 122 ], and wild ginseng root extract (HLJG0701- β ) inhibited AChE in vitro and in vivo [ 123 ]. Ginsenosides F1, Rd, Rk3, 20(S)-Rg3, F2, and Rb2 were found to possess strong AChE inhibitory activities [ 124 ].…”
Section: Modulation Of Cholinergic and Glutamatergic Neurotransmissio...mentioning
confidence: 99%
“…Notoginsenoside R1 increased choline acetyl transferase expression thereby increasing acetylcholine level, in an APP/PS1 double-transgenic mouse model of AD as compared to the vehicle-treated mice [ 121 ]. Polyacetylene compounds in hexane and methanol extracts of ginseng were reported to inhibit AChE [ 122 ], and wild ginseng root extract (HLJG0701- β ) inhibited AChE in vitro and in vivo [ 123 ]. Ginsenosides F1, Rd, Rk3, 20(S)-Rg3, F2, and Rb2 were found to possess strong AChE inhibitory activities [ 124 ].…”
Section: Modulation Of Cholinergic and Glutamatergic Neurotransmissio...mentioning
confidence: 99%
“…Panax ginseng is an ancient Korean and Chinese herbal medicine that has been used for thousands of years for the treatment of several diseases, including allergies, diabetes, hypertension, and cancer, with the ability to modulate neuronal calcium channels and immune modulation [ 44 ]. Not only animal studies [ 45 ] but also preclinical and clinical studies have confirmed the efficacy of the extract and powder and various ginsenosides of ginseng [ 46 ] on different NDDs, such as PD, AD, Huntington’s disease, ALS, and MS, through various mechanisms, including protection against neuronal toxicity, inhibition of caspase-3 and p-tau expression, and proinflammatory cytokines [ 47 ]. Improved AD scale, dementia, and mini-mental state scores have been documented after 12 weeks of using 9 gr/day Korean red ginseng powder or 4.5 gr/day Korean white ginseng powder [ 48 , 49 ].…”
Section: Antioxidant and Neuroprotective Agents Suggested For The Tre...mentioning
confidence: 99%
“…It has exhibited neurotherapeutic efficacy in treating multiple sclerosis (MS), amyotrophic lateral sclerosis (ALS), Parkinson’s, Huntington’s, and Alzheimer’s disease [ 64 ]. Ginsenosides have shown antioxidant effects in cell cultures and animal models [ 65 , 66 ]. Direct ROS scavenging effects and ligand-receptor signaling have been suggested as possible mechanisms by which ginsenoside (Rb1) exerts its antioxidant activity.…”
Section: Ginseng’s Immunomodulator Effectmentioning
confidence: 99%